Unravelling the mystery behind Kundt’s tube - Toh, Yan Xiong (2018)
The problem of the secondary peaks forming in Kundt’s tube has existed over a hundred years since August Kundt has invented the experiment in 1866. Therefore, the purpose of this study is to determine the reason behind the formation of secondary peaks in Kundt’s tube experiment. The approaches to this problem include (1) Setting up an actual Kundt’s tube experiment and study it under the high-speed camera and (2) Modelling the Kundt’s tube experiment in the COMSOL simulation and compute the time-dependent solution. One of the main conclusions suggested that the background air is moving in cluster collectively. Thus the background air should not be treated as a continuum medium. Given the fact that COMSOL computes the problem using finite element methods which rely on continuum equations, COMSOL may not be the suitable software for modelling the air background in Kundt’s tube experiment. Through analysing the data collected from the experiments, we came to a significant discovery that the average spacing is eigenfrequency independent and amplitude dependent. Although in this Final Year Project (FYP), the reason behind the phenomena of secondary peaks may still remain as a mystery, foundation work for comparison among Kundt’s tube experiment is made in this thesis. Furthermore, the results suggested that the air inside the tube may be moving in clusters collectively.